Параметрический синтез магистрального участка мультисервисной сети для предоставления услуг «Тriple рlay» - Евлаш, Д. В. (Eastern-European Journal of Enterprise Technologies, 2009)
Improved methods of parametric synthesis of the main plot multiservice network with selfincoming flow through the use of the method of penalty functions with exponential penalty algorithm and optimize